2014
DOI: 10.1111/hepr.12324
|View full text |Cite
|
Sign up to set email alerts
|

Nogo‐B: A potential indicator for hepatic cirrhosis and regulator in hepatic stellate cell activation

Abstract: Circulating Nogo-B may be an effective indicator for liver cirrhosis. Nogo-B inhibition could diminish HSC activation, in which alleviating ER stress may be one of the mechanisms, suggesting a potential approach to interference Nogo-B in liver fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 29 publications
2
26
0
Order By: Relevance
“…However, few new markers associated with prognosis or malignant behavior of ICC has been determined (Oishi et al 2012;Shimada et al 2010). In this study we studied Nogo-B, which has recently been identified as a potential marker of hepatic fibrosis (Zhang et al 2011;Gao et al 2013;Tashiro et al 2013;Men et al 2015) and as a potential enhancer of bile duct proliferation (Zhang Each survival rate is shown as % value, based on our analytical software.…”
Section: Macroscopic Findingmentioning
confidence: 99%
See 2 more Smart Citations
“…However, few new markers associated with prognosis or malignant behavior of ICC has been determined (Oishi et al 2012;Shimada et al 2010). In this study we studied Nogo-B, which has recently been identified as a potential marker of hepatic fibrosis (Zhang et al 2011;Gao et al 2013;Tashiro et al 2013;Men et al 2015) and as a potential enhancer of bile duct proliferation (Zhang Each survival rate is shown as % value, based on our analytical software.…”
Section: Macroscopic Findingmentioning
confidence: 99%
“…In the liver, Nogo-B is expressed specifically in cholangiocytes and non-parenchymal cells, but not in hepatocytes (Zhang et al 2011). Studies in cirrhotic patients and experimental models of fibrosis/cirrhosis suggest that Nogo-B is downregulated in liver fibrotic/cirrhosis or apoptosis of hepatic stellate cells Men et al 2015). Further, deletion of Nogo-B results in amelioration of liver cirrhosis and portal hypertension in mice with biliary cirrhosis Men et al 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although remarkable progress has been achieved in understanding the molecular mechanism and developing comprehensive therapies for HCC, rendering incurable HCC curable in certain patients, the prognosis of patients with HCC remains largely disappointing [14]. Nogo-B was reported to be preferentially expressed in non-parenchymal cells in the liver, and upregulation of Nogo-B expression has been detected in patients' cirrhotic liver tissues [15]. Nogo-B is potentially involved in the activation of hepatic stellate cells (HSCs), as knockdown of Nogo-B in HSCs dramatically impaired HSC activation [15].…”
Section: Introductionmentioning
confidence: 99%
“…Nogo-B was reported to be preferentially expressed in non-parenchymal cells in the liver, and upregulation of Nogo-B expression has been detected in patients' cirrhotic liver tissues [15]. Nogo-B is potentially involved in the activation of hepatic stellate cells (HSCs), as knockdown of Nogo-B in HSCs dramatically impaired HSC activation [15]. Nonetheless, the role of vascular endothelial Nogo-B in HCC progression remains unclear.…”
Section: Introductionmentioning
confidence: 99%